Trends and mechanisms of Russian disinformation concerning Poland: the analysis of information operations on Twitter in 2009-2020 - Paradowski, Rafał (The Copernicus Journal of Political Studies, 2025)
With the rise of social media, disinformation has become an important instrument in information warfare at the state level. The article aimed to determine the dominant directions of the Russian Federation’s disinformation and propaganda activities on the Internet concerning Poland and its citizens. The study used content made available as part of Twitter’s Information Operations project. It focused on the dynamics of the communication, the range of topics discussed and the emotions they evoke in recipients. From four databases containing almost 10 million tweets from 2009-2020, a sample related to Poland was extracted and analysed using data mining techniques. The findings showed that the discourse promoted by Russian services focused on undermining public trust, stoking social tensions and feeding anxiety. The impact of messages included both institutional (EU countries, NATO members) and interpersonal relationships (ethnic groups, representatives of professions, individuals). The research also illustrated the functioning of some disinformation mechanisms in practice. Its results may constitute a reference point for future studies of online hostile communication activities.